THE FEATURES OF USING INTERACTIVE METHODS IN THE PROCESS OF INCLUSIVE EDUCATION IN PRIMARY CLASSES - Shayunusova, Feruza (Журнал иностранных языков и лингвистики, 2023)
The issue of education and upbringing of children with disabilities or special needs is one of the most urgent issues of today. Inclusive education is a process of development of general education that ensures the opportunity for children with special needs to receive education, and assumes the existence of education for all in terms of adapting to the different needs of all children. Inclusive education is important for children with special needs to grow spiritually and physically, to achieve active participation in the life of society like all children. This article discusses the features and advantages of the inclusive education process, the specific aspects of using interactive methods in the inclusive education process.